The diagnostic utility of the Thwaites' system and lancet consensus scoring system in tuberculous vs. non-tuberculous subacute and chronic meningitis: multicenter analysis of 395 adult patients - Sulaiman, Tarek; Medi, Sai; Erdem, Hakan; Senbayrak, Seniha; Ozturk-Engin, Derya; Inan, Asuman; Hasbun, Rodrigo (Bmc, 2020)
Background Tuberculous meningitis (TBM) represents a diagnostic and management challenge to clinicians. The Thwaites' system and Lancet consensus scoring system are utilized to differentiate TBM from bacterial meningitis but their utility in subacute and chronic meningitis where TBM is an important consideration is unknown. Methods A multicenter retrospective study of adults with subacute and chronic meningitis, defined by symptoms greater than 5 days and less than 30 days for subacute meningitis (SAM) and greater than 30 days for chronic meningitis (CM). The Thwaites' system and Lancet consensus scoring system scores and the diagnostic accuracy by sensitivity, specificity, and area under the curve of receiver operating curve (AUC-ROC) were calculated. The Thwaites' system and Lancet consensus scoring system suggest a high probability of TBM with scores <= 4, and with scores of >= 12, respectively. Results A total of 395 patients were identified; 313 (79.2%) had subacute and 82 (20.8%) with chronic meningitis. Patients with chronic meningitis were more likely caused by tuberculosis and had higher rates of HIV infection (P < 0.001). A total of 162 patients with TBM and 233 patients with non-TBM had unknown (140, 60.1%), fungal (41, 17.6%), viral (29, 12.4%), miscellaneous (16, 6.7%), and bacterial (7, 3.0%) etiologies. TMB patients were older and presented with lower Glasgow coma scores, lower CSF glucose and higher CSF protein (P < 0.001). Both criteria were able to distinguish TBM from bacterial meningitis; only the Lancet score was able to differentiate TBM from fungal, viral, and unknown etiologies even though significant overlap occurred between the etiologies (P < .001). Both criteria showed poor diagnostic accuracy to distinguish TBM from non-TBM etiologies (AUC-ROC was <. 5), but Lancet consensus scoring system was fair in diagnosing TBM (AUC-ROC was .738), sensitivity of 50%, and specificity of 89.3%. Conclusion Both criteria can be helpful in distinguishing TBM from bacterial meningitis, but only the Lancet consensus scoring system can help differentiate TBM from meningitis caused by fungal, viral and unknown etiologies even though significant overlap occurs and the overall diagnostic accuracy of both criteria were either poor or fair.
Keywords: Tuberculous; Subacute; Meningitis; Thwaites; Lancet; Criteria